An Emotional Analysis of Articles in Languages of Different Systems - Mirzaahmedov Mirjalol Mansurjon ugli (European Science Publishing, 2023)
The article is devoted to the study of emotions in different languages of the system. One of the most pressing problems facing linguistics is the problem of expression. With these tools, the author can more accurately express his or her attitude toward the object being described.
Keywords: emotion, expressivity, communication tool, paradigmatic, psycholinguistics.